Non-colorectal liver metastases: A review of interventional and surgical treatment modalities - Kniepeiss, Daniela; Talakić, Emina; Portugaller, Rupert Horst; Fuchsjäger, Michael; Schemmer, Peter (Frontiers in Surgery, 2022)
Liver metastases (LM) occur in up to 90% either simultaneously with the diagnosis of the primary tumor or at a later time-point. While resection of colorectal LM and resection or transplantation of neuroendocrine LM is part of a standard therapy with a 5-year patient survival of up to 80%, resection of non-colorectal and non-neuroendocrine LM is still discussed controversially. The reason for it is the significantly lower survival benefit of all different tumor entities depending on the biological aggressiveness of the tumor. Randomized controlled trials are lacking. However, reviews of case series with ≥100 liver resections are available. They show a 5-year patient survival of up to 42% compared to only <5% in patients without treatment. Risk factors for poor survival include the type of primary tumor, a short interval between resection of the primary tumor and liver resection, extrahepatic manifestation of the tumor, number and size of the LM, and extent of liver resection. Overall, it has recently been shown that a good patient selection, the technical advances in surgical therapy and the use of a risk score to predict the prognosis lead to a significantly better outcome so that it is no longer justified not to offer liver resection to patients with non-colorectal, non- endocrine LM. Since modern therapy of LM is multimodal, the optimal therapeutic approach is decided individually by a multidisciplinary team consisting of visceral surgeons, oncologists, interventional radiologists and radiologists as part of a tumor board.